Safe Dosage of Caprine CSN1S2 Protein from Fresh Local Goat Milk for Rats Evaluated by Acute and Sub-Chronic Toxicity Testing - Fatchiyah Fatchiyah; Bambang Setiawan; Takeshi Ohta; Vita Agustina; Suharjono Suharjono (Journal of Mathematical and Fundamental Sciences, 2017)
Caprine milk CSN1S2 protein contains bioactive peptides that have a specific function in regulating the metabolic homeostasis mechanism between different organs. However, the safe dosage of goat milk consumption has not been established previously. The aim of this study was to evaluate the safe dosage of caprine CSN1S2 protein from fresh local goat milk using acute and repeated doses (for 4 weeks) in oral toxicity studies on three month old normal Wistar rats. The CSN1S2 protein was isolated from fresh goat milk. This casein protein administered in a single oral gavage dose to 5 rat groups at a daily dose of 0, 500, 1000, 2000, 4000 mg/kg BW for acute and 28-day sub-chronic toxicity testing of rats of both sexes. The result showed no evident mortality or abnormal effects. Data analysis of body weight, water and food intake, blood biochemical parameters, clinical observation and organ weight revealed no significant differences between all groups for both sexes. The weights of some organs showed differences between groups, but these values were within the normal weight ranges. The conclusion is that caprine CSN1S2 from fresh milk is safe for food consumption because there was no indication of toxicity, no mortality, and no hematological and clinical chemistry changes.